A permissive frame for unruliness: the educational structures of Ghanaian market fiction. Issue 2 (4th May 2018) - de Bruijn, Esther
Abstract: This article analyzes how, from the late 1990s into the mid-2000s, publishers and distributors of Ghana's market fiction for children took advantage of and manipulated educational structures in order to produce commercial sensations. The didacticism of the texts, aimed at satisfying educational demands, establishes a permissive frame for the unruliness of the fiction, both as an industry and as a literary genre. Market fiction producers and distributors look for gaps in the state provision of education and offer informal fixes to the contradictions at the core of national educational policy – the most pointed being the lack of adequate literature in schools. Drawing on book history methods, the essay shows how, at the industry's apex, its economic motive merged with educational aims to ultimately produce a genre for young readers that was affordable, accessible, and exciting in its novelty and cultural relevance. Three cases of figures in the industry who capitalize on the educational apparatus (two author–publishers and one educator–distributor) demonstrate how a popular literature can skirt institutional rules to the advantage of the industry and readerships alike. They also illustrate how the market fiction industry's commercial dreams are not anathema to literary innovation or even aesthetic brilliance.